Pengaruh Partisipasi Anggaran Dan Kejelasan Sasaran Anggaran terhadap Budgetary Slack Dengan Informasi Asimetri, Komitmen Organisasi, dan Budget Emphasis Sebagai Pemoderasi - Alek Murtin; Taufiq Bayu Septiadi (Journal of Accounting and Investment, 2011)
This study tries to understand the influences of (1) budget participation to budgetary slack, (2) budget goal clarity to budget slack, (3) asymmetry information on the relation of budget participation as well as budgetary slack, (4) organizational commitment on the relation of budget participation as well as  budgetary slack, (5) budget emphasis on the relation of budget participation as well as  budgetary slack, (6) asymmetry information on the relation of budget goal clarity as well as  budgetary slack, (7) organizational commitment on the relation of budget goal clarity as well as  budgetary slack, (8) budget emphasis on the relation of budget goal clarity as well as  budgetary slack. The subjects of this study are middle and lower managers in local government instutions including section/department/sub-section head, under the municipality and regencies in the city government of Yogyakarta. The results show, (1) budget participation influences to budgetry slack, (2) budget goal clarity influences to budgetry slack, (3) asymmetry information act as moderating variable in the relation of budget participation with budgetary slack, (4) organizational commitment act as moderating variable in the relation of budget participation with budgetary slack.